Board gender diversity and environmental innovation: the role of time horizons and SEW in Chinese family firms - Zhai, Zhe (Frontiers in Sustainability, 2026)
This study examines whether, and under what conditions, board gender diversity fosters environmental innovation in Chinese listed family firms. Using panel data for 2010–2022 and two-way firm and year fixed-effects models, we find that higher board gender diversity is associated with modest but statistically robust increases in subsequent green patenting. The association is stronger in firms with longer leadership tenures, weaker in heavily polluting industries, and only weakly differentiated by donation-based proxies for socioemotional-wealth salience. Interpreted through a behavioral corporate-governance lens, the results highlight the role of organizational patience, stakeholder sensitivity, resource stewardship and reputation-oriented motives in translating board composition into substantive green technological change. Overall, board gender diversity appears to operate as a governance complement whose effectiveness depends on time horizons and sectoral constraints, implying that complementary policy and financial instruments are needed to realize similar gains in hard-to-abate sectors.JEL codesO32, G34, Q55, M14, J16.